2022
DOI: 10.7759/cureus.27459
|View full text |Cite
|
Sign up to set email alerts
|

Novel Scoring Systems to Predict the Need for Oxygenation and ICU Care, and Mortality in Hospitalized COVID-19 Patients: A Risk Stratification Tool

Abstract: Introduction: A rapid surge in cases during the COVID-19 pandemic can overwhelm any healthcare system. It is imperative to triage patients who would require oxygen and ICU care, and predict mortality. Specific parameters at admission may help in identifying them.Methodology: A prospective observational study was undertaken in a COVID-19 ward of a tertiary care center. All baseline clinical and laboratory data were captured. Patients were followed till death or discharge. Univariable and multivariable logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In patients diagnosed with SARS-CoV-2 infection, higher CRP levels have been associated with severe pulmonary pathology and with worse overall outcomes [12][13][14][15][16][18][19][20][21][22]. Moreover, elevated CRP has been used as a predictor of COVID-19 severity and mortality [5][6][7][8][9][10][11]. However, patients with SARS-CoV-2 present for medical attention at differing points in their illness [47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients diagnosed with SARS-CoV-2 infection, higher CRP levels have been associated with severe pulmonary pathology and with worse overall outcomes [12][13][14][15][16][18][19][20][21][22]. Moreover, elevated CRP has been used as a predictor of COVID-19 severity and mortality [5][6][7][8][9][10][11]. However, patients with SARS-CoV-2 present for medical attention at differing points in their illness [47].…”
Section: Discussionmentioning
confidence: 99%
“…However, using MAX CRP over the first 5 days of hospitalization is appropriate given that 71% of patients in our cohort spent at least 5 days in the hospital (median 8 [IQR: 4-12] days). Patients who died stayed longer (10)(11)(12)(13)(14)(15)(16)(17) days) than patients who survived (7)(8)(9)(10)(11) days; p < 0.001), with 84.2% of patients who died staying at least 5 days, vs. 67.6% of patients who survived (p < 0.001). Therefore, regardless of hospitalization outcome, most patients had sufficiently long hospitalizations for a maximum CRP value over 5 days to be relevant.…”
Section: Relationship Of Crp Levels To Covid-19 Patients' Deathmentioning
confidence: 96%
See 1 more Smart Citation
“…In total, 13 studies have been published this year alone (2022) that independently showed that higher NLR in COVID-19 patients entering the hospital was a strong predictor of in-hospital worsening or death [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Chart review showed this to be the case also at our ICU, independently of whether dapsone was given or not.…”
Section: Discussionmentioning
confidence: 99%